Disturbed Amino Acid Metabolism in HIV: Association with Neuropsychiatric Symptoms - Gostner, Johanna M.; Becker, Kathrin; Kurz, Katharina; Fuchs, Dietmar (Frontiers in Psychiatry, 2015)
Blood levels of the amino acid phenylalanine, as well as of the tryptophan breakdown product kynurenine, are found to be elevated in human immunodeficiency virus type 1 (HIV-1)-infected patients. Both essential amino acids, tryptophan and phenylalanine are important precursor molecules for neurotransmitter biosynthesis. Thus, dysregulated amino acid metabolism may be related to disease-associated neuropsychiatric symptoms such as development of depression, fatigue, and cognitive impairment. Increased phenylalanine/tyrosine and kynurenine/tryptophan ratios are associated with immune activation in patients with HIV-1 infection and decrease upon effective antiretroviral therapy. Recent large-scale metabolic studies have confirmed the crucial involvement of tryptophan and phenylalanine metabolism in HIV-associated disease. Herein, we summarize the current status of the role of tryptophan and phenylalanine metabolism in HIV disease and discuss how inflammatory stress-associated dysregulation of amino acid metabolism may be part of the pathophysiology of common HIV-associated neuropsychiatric conditions.